High frequency of antibiotic resistance in organisms isolated from blood cultures among pediatric patients in a public hospital with limited resources in the northern Dominican Republic - Santana-Chalas Genara; Despradel Omar; Rivas Alicia; Robles Yaniris; Cruz Carmen Ynelsa; Griselda Escobedo-Melendez (Journal of the Pediatric Infectious Diseases Society, 2026)
Abstract Background Bloodstream infections (BSIs) are a significant cause of morbidity and mortality in pediatric patients. The World Health Organization (WHO) estimates that three million children develop sepsis each year, with mortality rates between 11% and 19%. In Latin American countries, Klebsiella pneumoniae, Escherichia coli, and Staphylococcus aureus are the most common causes of BSIs, and antibiotic resistance represents an important challenge. However, in the Dominican Republic, data on this topic are scarce due to the previous lack of equipment for organism identification and antimicrobial susceptibility testing before 2023-year. We aimed to analyze the organisms isolated from blood cultures and their antimicrobial susceptibility patterns among hospitalized pediatric patients. Methods In this retrospective cross-sectional study, a total of 380 positive blood cultures from pediatric patients (<18 years old) treated at Hospital Dr. Arturo Grullón were included between January 2023 and December 2024. Contaminated cultures were excluded. The following data were collected: isolated organisms, their susceptibility and resistance profiles, and the hospital ward where the patient was admitted. Blood cultures and antimicrobial susceptibility testing were performed using BacT/ALERT® and VITEK® systems. A descriptive statistical analysis was conducted. The Institutional Review Board approved this study. Results We identified a high frequency of extended-spectrum beta-lactamase (ESBL)–producing K. pneumoniae (74.2%) and E. coli (55%), as well as AmpC expression in E. cloacae. Susceptibility to carbapenems and amikacin was observed in more than 90% of strains. High resistance to oxacillin was detected in S. epidermidis and S. hominis (95%), while susceptibility to cefoxitin was found in S. aureus and S. epidermidis (70% and 85%, respectively). All these strains were 100% susceptible to vancomycin. Most pediatric patients were admitted to the neonatal and pediatric intensive care units, emergency, or burn units. Conclusion Our results provide an overview of the frequency of organisms isolated from blood cultures and their antimicrobial susceptibility/resistance patterns in a resource-limited hospital. Initial empirical antimicrobial therapy for pediatric patients with BSIs should include fourth-generation cephalosporins and carbapenems for Gram-negative bacteria, and vancomycin for Gram-positive bacteria.